hrHPV prevalence and type distribution in rural Zimbabwe: A community-based self-collection study using near-point-of-care GeneXpert HPV testing - Megan B. Fitzpatrick; Racheal S. Dube Mandishora; David A. Katzenstein; Kathy McCarty; Jenna Weber; Malaya K. Sahoo; Justen Manasa; Zvavahera Mike Chirenje; Benjamin A. Pinsky (International Journal of Infectious Diseases, 2019)
Objectives: High-risk human papilloma viruses (hrHPV) are the causative agents of cervical cancer, the leading cause of cancer deaths among Zimbabwean women. The objective of this study was to describe the hrHPV types found in Zimbabwe for consideration in cervical cancer screening and vaccination efforts. Design and methods: To determine hrHPV prevalence and type distribution in Zimbabwe we implemented a community-based cross-sectional study of self-collected cervicovaginal samples with hrHPV screening using near-point-of-care Cepheid GeneXpert HPV. Results: The hrHPV prevalence was 17% (112/643); 33% (41/123) vs. 14% (71/520) among HIV-1-positive and -negative participants, respectively (p = 2.3E-07). Typing via Xpert HPV showed very good overall agreement (77.2%, kappa = 0.698) with the Seegene Anyplex II HPV HR Detection kit. The most common types were HPV16, HPV18, HPV35, HPV52, HPV58, HPV68, HPV18, and HPV51, each of which appeared in 14–20% of infections. 37% (28/76) of women with positive cytology results (ASCUS+) had a type not included in the basic vaccine and 25% (19/76) had a type not currently in the nine-valent vaccine. Conclusions: hrHPV type distribution includes less common high-risk types in rural Zimbabwe. The distribution and carcinogenicity of hrHPV type distribution should be considered during screening assay design, program development, as well as vaccine distribution and design. Keywords: Human Papillomavirus, Cervical cancer screening, Self-collection